Pharmacokinetics and pharmacodynamics of intravenous artesunate during severe malaria treatment in Ugandan adults - Byakika-Kibwika, Pauline (BioMed Central, 2012)
BACKGROUND: Severe malaria is a medical emergency with high mortality. Prompt achievement of therapeutic concentrations of highly effective anti-malarial drugs reduces the risk of death. The aim of this study was to assess the pharmacokinetics and pharmacodynamics of intravenous artesunate in Ugandan adults with severe malaria. METHODS: Fourteen adults with severe falciparum malaria requiring parenteral therapy were treated with 2.4 mg/kg intravenous artesunate. Blood samples were collected after the initial dose and plasma concentrations of artesunate and dihydroartemisinin measured by solid-phase extraction and liquid chromatography-tandem mass spectrometry. The study was approved by the Makerere University Faculty of Medicine Research and Ethics Committee (Ref2010-015) and Uganda National Council of Science and Technology (HS605) and registered with ClinicalTrials.gov (NCT01122134). RESULTS: All study participants achieved prompt resolution of symptoms and complete parasite clearance with median (range) parasite clearance time of 17 (8–24) hours. Median (range) maximal artesunate concentration (C(max)) was 3260 (1020–164000) ng/mL, terminal elimination half-life (T(1/2)) was 0.25 (0.1-1.8) hours and total artesunate exposure (AUC) was 727 (290–111256) ng·h/mL. Median (range) dihydroartemisinin C(max) was 3140 (1670–9530) ng/mL, with T(max) of 0.14 (0.6 – 6.07) hours and T(1/2) of 1.31 (0.8–2.8) hours. Dihydroartemisinin AUC was 3492 (2183–6338) ng·h/mL. None of the participants reported adverse events. CONCLUSIONS: Plasma concentrations of artesunate and dihydroartemisinin were achieved rapidly with rapid and complete symptom resolution and parasite clearance with no adverse events.